Assessing HPV vaccination perceptions with online social media in Italy. (March 2019) - Angioli, Roberto; Casciello, Massimo; Lopez, Salvatore; Plotti, Francesco; Minco, Lidia Di; Frati, Paola; Fineschi, Vittorio; Panici, Pierluigi Benedetti; Scaletta, Giuseppe; Capriglione, Stella; Miranda, Andrea; Feole, Laura; et al.
Abstract : Objective: Because of the widespread availability of the internet and social media, people often collect and disseminate news online making it important to understand the underlying mechanisms to steer promotional strategies in healthcare. The aim of this study is to analyze perceptions regarding the human papillomavirus (HPV) vaccine in Italy. Methods: From August 2015 to July 2016, articles, news, posts, and tweets were collected from social networks, posts on forums, blogs, and pictures about HPV. Using other keywords and specific semantic rules, we selected conversations presenting the negative or positive perceptions of HPV. We divided them into subgroups depending on the website, publication date, authors, main theme, and transmission modality. Results: Most conversations occurred on social networks. Of all the conversations regarding HPV, more than 50% were about vaccination. With regard to conversations exclusively on the HPV vaccine, 47%, 32%, and 21% were positive, negative and neutral, respectively. Only 9% of the conversations mentioned the vaccine trade name and, in these conversations, perception was almost always negative. We observed many peaks in positive conversation trends compared with negative trends. The peaks were related to the web dissemination of particular news regarding HPV vaccination. Conclusions: In this study we have shown how mass media influences the diffusion of both negative and positive perceptions about HPV vaccines and suggest better ways to inform people about the importance of HPV vaccination.